T & T Clark companion to Reformation theology - Whitford, David M. (David Mark) (T & T Clark companions., 2012)
This volume introduces the main theological topics of Reformation theology in a language that is clear and concise. Theology in the Reformation era can be complicated and contentious. This volume aims to cut through the theological jargon and explain what people believed and why. The book begins with an essay that explains to students how one can approach the study of 16th century theology. It includes a guide to major events, persons, doctrines, and movements.